Prospects of News Televsion: Materials of In-Depth Interviews - I. I. Volkova; E. L. Proskurnova; T. T. D. Tran (Научный диалог, 2021)
The issues of the development of traditional news television in the context of a single information space are considered. The goal is to look at how much content creators and consumers agree in their predictions about the future of TV. The data of in-depth interviews were used as empirical material: professional television journalists (federal TV channels) and students (PFUR “Television” department) were interviewed. The contradictions between the two basic types of media consumption, which are characteristic of addressers and addressees of television messages, are revealed. It is shown that these contradictions explain the generational gap in the perception of modern news television programs, predetermine the decrease in TV consumption of news content from federal channels designed for a mass audience. The relevance of the work is due to the rethinking of the functions and prospects for the development of traditional TV by both professional broadcasters and consumers. The conclusion is made about the further development of news television. It is noted that, on the one hand (the opinion of professionals), traditional television broadcasting will be preserved while adjusting the agenda, rethinking interaction with the audience, changing the broadcasting paradigm, mastering new competencies by professional journalists and using the opportunities of the online space. On the other hand (students’ opinion), subject-to-object news broadcasting of federal channels will cease to exist when the generation of viewers and the funding model change.